Theoretical limits of the multistacked 1D and 2D microstructured inorganic solar cells - Yengel, Emre; Karaağaç, H.; Logeeswaran, V. J.; İslam, M. S. (SPIE, 2015)
Recent studies in monocrystalline semiconductor solar cells are focused on mechanically stacking multiple cells from different materials to increase the power conversion efficiency. Although, the results show promising increase in the device performance, the cost remains as the main drawback. In this study, we calculated the theoretical limits of multistacked 1D and 2D microstructered inorganic monocrstalline solar cells. This system is studied for Si and Ge material pair. The results show promising improvements in the surface reflection due to enhanced light trapping caused by photon-microstructures interactions. The theoretical results are also supported with surface reflection and angular dependent power conversion efficiency measurements of 2D axial microwall solar cells. We address the challenge of cost reduction by proposing to use our recently reported mass-manufacturable fracture-transfer- printing method which enables the use of a monocrystalline substrate wafer for repeated fabrication of devices by consuming only few microns of materials in each layer of devices. We calculated thickness dependent power conversion efficiencies of multistacked Si/Ge microstructured solar cells and found the power conversion efficiency to saturate at 26% with a combined device thickness of 30 μm. Besides having benefits of fabricating low-cost, light weight, flexible, semi-transparent, and highly efficient devices, the proposed fabrication method is applicable for other III-V materials and compounds to further increase the power conversion efficiency above 35% range.
Keywords: Solar cells; Silicon; Multistacked PV; Inorganic solar cells; Thin films; Monocrystalline semiconductors; Si/Ge solar cell; Power conversion efficiencies; Transfer printing; Silicon wafers; Cost reduction; Silicon solar cells; Microstructure; D and 2-D microstructure; Germanium; Surface reflections; Fracture-transfer-printing; Costs; Fracture; Printing; Conversion efficiency; Monocrystalline substrates; Si/Ge